Expressions of abandonment : exploring abandonment as visual inspiration - Ros Farzana Roskhaider (Nanyang Technological University, 2021)
In recent years, there has been an increased interest in the exploration and study of abandoned sites within the discipline of heritage studies. The very act of visiting abandoned spaces has become so widely recognised that there’s a global term for it — Urban exploration, or UrbEx for short. Urban explorers see through extensive documentation and projects such as UrbEx photography and videography, in hopes of commemorating the historic aspect of these sites — but despite this, there is a lack of study of abandonment itself within these forsaken spaces. The project aims to bridge this gap by using the visuals of abandonment as a driving force to inspire new designs and celebrate the beauty in abandonment. Ultimately, this project aims to encourage interest and bring awareness towards these abandoned spaces by transforming how they can be perceived; particularly through the study and documentation of 6 visual elements — colour, architecture, textures, marks, typography and symbols.